2010
DOI: 10.1002/jso.21769
|View full text |Cite
|
Sign up to set email alerts
|

Is the need for an arterial resection a contraindication to pancreatic resection for locally advanced pancreatic adenocarcinoma? a case‐matched controlled study

Abstract: Pancreatic resections with AR for adenocarcinoma allowed to obtain a 3-survival rate similar to that of a matched group of patients not requiring AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 43 publications
1
38
1
2
Order By: Relevance
“…14 of the remaining 35 studies (Kim et al, 2006;Murakami et al, 2008;Balentine et al, 2010;Chu et al, 2010;Kanda et al, 2010;de Jong et al, 2011;Jamieson et al, 2011;Kneuertz et al, 2011;Maithel et al, 2011;Singal et al, 2011;Chatterjee et al, 2012;Watanabe et al, 2012;Xie et al, 2012;Fisher et al, 2013) were excluded because they were reported by the same institutions as other studies. 21 studies (Ozaki et al, 1999;Mitsunaga et al, 2005;Nakagohri et al, 2006;Pawlik et al, 2007;Kazanjian et al, 2008;Kato et al, 2009;Nagai et al, 2009;Sergeant et al, 2009;Ben et al, 2010;Murakami et al, 2010;Bachellier et al, 2011;Kim et al, 2011;Schiffman et al, 2011;Cheng et al, 2012;Jamieson et al, 2012;Lee et al, 2012;Murata et al, 2012;Sahin et al, 2012;Takahashi et al, 2012;Turrini et al, 2013;Xie et al, 2013) were included in the final meta-analysis, comprising one case matched controlled study and 20 retrospective cohort studies (Table 1). A total of 4459 patients were included in this meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 of the remaining 35 studies (Kim et al, 2006;Murakami et al, 2008;Balentine et al, 2010;Chu et al, 2010;Kanda et al, 2010;de Jong et al, 2011;Jamieson et al, 2011;Kneuertz et al, 2011;Maithel et al, 2011;Singal et al, 2011;Chatterjee et al, 2012;Watanabe et al, 2012;Xie et al, 2012;Fisher et al, 2013) were excluded because they were reported by the same institutions as other studies. 21 studies (Ozaki et al, 1999;Mitsunaga et al, 2005;Nakagohri et al, 2006;Pawlik et al, 2007;Kazanjian et al, 2008;Kato et al, 2009;Nagai et al, 2009;Sergeant et al, 2009;Ben et al, 2010;Murakami et al, 2010;Bachellier et al, 2011;Kim et al, 2011;Schiffman et al, 2011;Cheng et al, 2012;Jamieson et al, 2012;Lee et al, 2012;Murata et al, 2012;Sahin et al, 2012;Takahashi et al, 2012;Turrini et al, 2013;Xie et al, 2013) were included in the final meta-analysis, comprising one case matched controlled study and 20 retrospective cohort studies (Table 1). A total of 4459 patients were included in this meta-analysis.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Involvement of the celiac, hepatic, or superior mesenteric arteries has commonly been considered a contraindication to resection of locally advanced pancreatic cancer (Mollberg et al, 2011). One included study (Bachellier et al, 2011) was reported that 34 patients underwent an extended pancreatic resection with arterial resection. We included the study because it corresponded to "resecected pancreatic cancer".…”
Section: 5133 Influence Of Perineural Invasion On Survival and Recurmentioning
confidence: 99%
“…Some studies doubted the question whether performing of arterial resection in patients with pancreatoduodenectomy is necessary because the procedure itself is a technical challenge. They confirmed that the arterial resection is possible, but there were not enough data in favor, and that is why it is applied in the context of randomized controlled trials (RCTs) [25].…”
Section: Arterial Resectionsmentioning
confidence: 99%
“…The author believes that PVR should become a standard procedure during PD. Furthermore, there are many publications describing more aggressive types of resections in selected groups of patients including arterial resection, but are not considered routine and thus cannot yet be recommended (11,12,13).…”
Section: Scope Of Current Opinionsmentioning
confidence: 99%